Comparison of the limb-lead electrocardiogram to the 12-lead electrocardiogram for identifying conditions associated with sudden cardiac death in youth athletes - Le, H. M.; Downey, B. C.; Lanois, C. J.; Miller, P. E.; Stein, C. J.; Kerkhof, D. L.; Corrado, G. D. (The American Journal of Cardiology, 2020)
Highlights: